Pengaruh Pendidikan Kesehatan Dengan Metode Ceramah Plus Diskusi Dan Tugas (CPDT) Terhadap Pengetahuan Dan Sikap Remaja Putri Tentang Pencegahan Keputihan Di SMPN 29 Surabaya - Erlita Kusuma R (Akademi Keperawatan Dharma Husada Kediri, 2012)
Flour albus incidents increase every year. Flour albus is a normal condition but it will be dangerous if flour albums becomes ill smelling, color of fluid, itching, and in a large amount. The low level of the female teenagers knowledge about flour albus prevention will cause negative attitudes. Lecture plus discussion and assignment (CPDT) methods used to accompany respondents on health education. This method was expected to change the knowledge and attitude of persons in order to increase his health quality. The research used pre experimental with one group pre post test design. Population subject of this research is the female teenagers. Questioner filled before and after the researcher give lecture plus discussion and assignment (CPDT) method to 14 respondents who fulfil the inclusion criteria. Independent variable is health education with lecture plus discussion and assignment (CPDT) method. Dependent variable is female teenagers knowledge and attitude. Data was collected and then analyzed by using Wilcoxon Signed Rank Test with significant value p≤ 0.05. `This results showed that there was effect of lecture plus discussion and assignment (CPDT) method on the female teenagers knowledge and attitude about flour albus prevention. Based on that results we can concluded that the lecture plus discussion and assignment (CPDT) method can be able to increase knowledge (p=0,001) and attitude (p=0,002). Adequate and effective information through lecture plus discussion and assignment (CPDT) method can increase knowledge. It will influence the positive attitude and action at daily activity. Hopefully, this research impact on decresing number of flour albus incidens in female teenagers through an effective health education methods.